Novel sulfated phosphoglycolipids from Natronomonas moolapensis. (October 2015) - Hoffmann, Andreas; Kovermann, Michael; Oberwinkler, Tanja; Siedler, Frank; Cortina, Niña Socorro; Balbach, Jochen; Oesterhelt, Dieter
Highlights: Uncharacterized glycolipid species from the halophilic archaeon Natronomonas moolapensis were identified and purified. An unusual glycolipid core structure based on phosphatidylglycerol was identified by MS and NMR. Two mono-glycosyl moieties, d -glucopyranose-6-sulfate andd -galactofuranose-6-sulfate, respectively, were identified. Abstract: Polar lipid pattern determination is often used for the taxonomic classification of halophilic Archaea in addition to a genomic characterization. During the analysis of polar lipid extracts from the recently described haloarchaeon Natrononomonas moolapensis, an unknown glycolipid was detected. Fragmentation patterns observed from preliminary mass spectrometric analysis initially suggested the presence of a sulfo-hexosyl-phosphatidylglycerol. However, by NMR spectroscopy and enzymatic assays the existence of two isomeric molecules with different hexoses (1-(6-sulfo-d -glcp/galf-β1, 2-glycero)-phospho-2, 3-diphytanylglycerol) could be shown. The structural origin from phosphatidylglycerol distinguishes these glycolipids within Archaea, because all other characterized haloarchaeal glycolipids consist of diphytanylglycerol directly linked to an oligoglycosyl moiety. Now the door is open to investigate the physical and functional consequences of these architectural differences of the head groups.